2021
DOI: 10.5430/ijhe.v11n1p100
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Challenges of Implementing An Integrated Talent Management Strategy at A Tertiary Institution in South Africa

Abstract: The aim of this study was to investigate and delineate the perceived challenges of implementing an integrated talent management strategy at a South African tertiary institution. The study was conducted at a relatively new university that opened its doors on the 1st of January 2015. Since the inception of the university under study, the institution has grown considerably but without proper policies and strategies in place to ensure its competitiveness and sustainability within the current Higher Education and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Higher education institutions in SA face immense difficulties in terms of skilled human resources and retention of their valuable and skilled employees, which has a devastating effect on the successful functioning of these institutions (Abugre, 2018;Barkhuizen et al, 2020;Deas, 2018;Erasmus et al, 2015;Gerstein & Friedman, 2016;Mukwawaya, 2022;Musakuro, 2022;Robyn, 2012;Tettey, 2006). Previous research suggests that there may be as much as a 13% shortage of academic and support staff at HEIs (Abugre, 2018;Deas & Coetzee, 2020;Dewhurst et al, 2013).…”
Section: Staff Retention In the Higher Education Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher education institutions in SA face immense difficulties in terms of skilled human resources and retention of their valuable and skilled employees, which has a devastating effect on the successful functioning of these institutions (Abugre, 2018;Barkhuizen et al, 2020;Deas, 2018;Erasmus et al, 2015;Gerstein & Friedman, 2016;Mukwawaya, 2022;Musakuro, 2022;Robyn, 2012;Tettey, 2006). Previous research suggests that there may be as much as a 13% shortage of academic and support staff at HEIs (Abugre, 2018;Deas & Coetzee, 2020;Dewhurst et al, 2013).…”
Section: Staff Retention In the Higher Education Contextmentioning
confidence: 99%
“…These factors comprise: compensation, job characteristics, opportunities for training and development, supervisor support, career opportunities, and work-life balance policies. Thus, effective capacity building, and staff retention along with the type of relationship which progresses between diverse groups of employees and their employers, will ultimately determine the success of HEIs (Armstrong & Taylor, 2014;Festing & Schäfer, 2014;Guo, 2017;Mukwawaya, 2022;Snyman, 2022). Employees are one of the most important assets of any organisation, and in order to ensure the success and efficient functioning of these institutions, it is imperative for HEIs to develop and implement retention practices which take the needs of various socio-demographic groups into account.…”
Section: Staff Retention In the Higher Education Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Mukwawaya, Pronches and Green (2022) investigated and delineated the perceived challenges of implementing an integrated management strategy at a South African tertiary institution. The results of the study indicated that the major challenges experienced in implementing the TM strategy include lack of management commitment and budget, as well as unionism and resistance to change amongst employees (Mukwawaya et al, 2022).…”
Section: Talent Management Challenges In South Africamentioning
confidence: 99%